Meta-analisis efektifitas model inkuiri terbimbing terhadap keterampilan proses sains dan kemampuan berfikir kritis peserta didik - Annisa Kurniawti; Festiyed Festiyed; Asrizal Asrizal (PILLAR OF PHYSICS EDUCATION, 2019)
This research aims to analyze the effectiveness of guided inquiry models of science process skills and critical thinking abilities of students viewed from the level of education, learning materials, and teaching materials used. This research method is a meta-analysis method. The research sample is taken from 10 (ten) national thesis journals that both use the guided inquiry model. The results of this meta-analysis research are the guided inquiry model seen from the level of education, that is, the guided inquiry model is equally effective at the secondary and secondary education level. Viewed from the learning material, the guided inquiry model is more effective on the material pressure to improve students 'science process skills, and the guided inquiry model is more effectively taught on simple aircraft material to improve students' critical thinking abilities. Judging from the teaching materials used, the guided inquiry model is more effectively taught with teaching materials in the form of student worksheets and student books to improve students 'science process skills, and the guided inquiry model is more effective when taught with the media to improve students' critical thinking skills